Peer Flipped Learning in Financial Mathematics: Enhancing Academic Achievement and Mathematical Thinking in College of Science Students - Nasser H. Youssef; Essa A. Alibraheim; Osama H. Helal; Manal I. AlOhali (Migration Letters, 2023)
This research employed a quasi-experimental design to investigate the impact of Peer Flipped Learning (PFL) on academic achievement (AA) and mathematical thinking (MT) among mathematics department students at Imam Abdulrahman Bin Faisal University’s College of Science, Saudi Arabia. Two assessment tools were employed: an AA test for the financial mathematics course and an MT test. A sample of 70 students was randomly divided into an experimental group (n=35) exposed to PFL and a control group (n=35) taught through traditional methods in a financial mathematics course. Results from post-assessment AA and MT tests revealed statistically significant differences, favoring the experimental group. These findings highlight the efficacy of PFL as a modern teaching strategy for enhancing university-level mathematics education and underscore the importance of training educators in its implementation to foster students’ academic achievement and critical thinking skills.